Planung in unbekannten Gewässern: Räumliche Transformationen, Planungswandel und rollenreflexive Planung - Lamker, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
For planners, processes of complex spatial transformations today are comparable to uncharted land and an uncertain voyage. Many possible role images overlap and contrast to traditional and established ways of thinking and acting. The focus here is on navigating instead of controlling, about supporting instead of enforcing. Planning lacks tools to think and act when facing uncertainty. This paper proposes role-reflexive planning as an educational and experimental approach to thinking through different potentialities. It offers groundwork from the boundary between planning and transition studies, using role-based ideas as a bridge. It offers an overview about different roles that are relevant to working towards transformations as spatial planners. It develops an account of role-reflexive planning that connects between contexts, actions and back to individual modes of behaviour in planning processes. As a basis, this paper condenses experiences of a role-playing pilot workshop and discussions about potential elements of a transition towards ’post-growth planning’. It outlines how role-playing challenges the individual roles of actors beyond the game situations themselves. Conceptual ideas foster a renewed role-based debate on thinking and acting in the face of uncertainty and ways to navigate through the stormy waters of transformation.